Analysis of Students' Mathematical Connection Ability Through Learning Strategies Based on Local Wisdom - Andi Muhammad Irfan Taufan Asfar; Sumiati Sumiati; Andi Muhamad Iqbal Akbar Asfar; Andi Nurannisa (Didaktik Matematika, 2022)
Students' mathematical abilities are still considered low due to the lack of students' mathematical connection abilities. One effort that can be done in overcoming the low ability of students' mathematical connections is to involve the culture around students in the learning process. This study aims to analyze students' mathematical connection ability through the application of learning strategies based on local wisdom a'bulo sibatang, assamaturu, mappesabbi and sipakatau. The research method used is a quantitative quasi-experimental type of nonequivalent control group design. Through purposive sampling technique, it was obtained class XI MIPA 3 (experimental class) and XI MIPA 1 (control class). The instrument used is a test to indicators of mathematical connection ability. The results showed an increase in indicator of mathematical connection ability in the experimental class, namely 88.52% indicator I, 85.35% indicator II and 83.87% indicator III. Meanwhile, in the control class applied problem-based learning strategies only got a score of 65%. Based on the results of the analysis, it can be concluded that local wisdom-based learning in the experimental class is able to improve students' mathematical connection ability better than the control class that applies problem-based learning.